تأثير التدريب الذهني المصحوب بتداخل التمرين المتسلسل والمتغير في تعلم بعض المهارات الأساسية بالكرة الطائرة للطالبات والاحتفاظ بها - غفور, توانا وهبي (Sulaimani Journal for Humanities, 2021)
The purpose of the study is to identify the impacts of indirect mental training combined with the overlapping of the sequential and variable exercise between the tribal and dimensional tests in learning some basic volleyball skills (over-the-top handling forward, bottom-up reception, front-facing transmissions from below) to female students. The study also aims at investigating the differences between the research groups in dimensional tests, as well as identifying the differences in computational circles between the three retention research groups. The researcher used the experimental method, and purposive sampling to recruit the participants of the study who are students of the third academic year at the Faculty of Physical Education and Sports Science at the University of Sulaymaniyah (N=21). The educational curriculum is used for the purpose of the study which consists of 15 units per group, with two educational units per week, the time of each educational unit is 90 minutes, and the time of indirect mental training 6 minutes per skill, the amount of 3 minutes at the beginning of the application activity of the main section, and 3 the other minutes after the passage of 30 minutes of the start of the application activity of the main section. The results of the study reveal that the use of indirect mental training accompanied by overlap of sequential and variable exercise, and the combination of them also has a positive and effective effect in learning some basic volleyball skills for female students. The researcher recommended the need to use indirect mental training accompanied by overlapping and variable sequential exercise because it has an effective effect on the investment of time and effort.
Keywords: mental training; Sequential Exercise; Varied Exercise; Volleyball; Retention